Description Of Health Workers At The Soropia Health Center And The Morosi Health Center, Konawe District: Health Workers - Muhammad Ikhsan Akbar; Hartian Dode; Yuliana Muslimin; Sri Mulyani (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Efforts to meet the need for health workers have not yet taken into account the conditions of the number, type, quality and distribution. The availability of health workers is still an important highlight due to the uneven distribution. Based on initial survey data at the Morosi Health Center, the number of health workers was 46 health workers. For the Soropia Health Center, the number of health workers is 57 health workers. The purpose of this study was to describe the need for health workers at the Morosi Health Center and Soropia District Health Center Method: This study uses a descriptive approach using the Minimum Tenacity Standard method. This research will be conducted in June 2023. The research was conducted at the Morosi Puksemsas and the Soropia Health Center, Konawe Regency, Southeast Sulawesi. The primary data source in this study is data obtained from research samples using the Minimum Power Standards method. Determination of Public Health Center was carried out by porpusive sampling. The data analysis technique in this study used the analysis of Minimum Employment Standards at the Community Health Centers based on the Standards issued by the Ministry of Health Results: Soropia Health Center, Konawe District. there is a shortage of dentists and medical laboratory personnel at the Soropia Health Center. The results of the study also showed that there were excesses of some health workers. The data shows that there is an excess of 24 nurses, an excess of 15 midwives, an excess of 3 nutritionists, and an excess of 2 pharmacists. The Morosi Health Center, Konawe Regency, has a shortage of Environmental Sanitation Workers at the Morosi Health Center. The results of the study also showed that there were excesses of some health workers. The data shows that there is an excess of 10 nurses, an excess of 12 midwives, an excess of 5 personnel for Health Promotion and Behavioral Sciences, an excess of 4 pharmacists, an excess of 2 nutritionists, and an excess of 2 medical laboratory personnel. Conclusion: Morosi Health Center and Soropia Health Center still have a shortage and excess of health workers. It is hoped that the regional government of Konawe Regency will use health workload analysis in the future in planning health workers because this will better answer the needs of health workers needed in each Public Health Center.